Pengembangan CD Pembelajaran Matematika Berbantuan Software Geometer’s Sketchpad dengan Pendekatan Kontruktivisme Berbasis Teori Jean Piaget - Sidabutar, Sutri Theo Lija (Unika Santo Thomas Medan, 2019)
This study aims to 1) determine the validity of the Mathematics learning CD assisted by Geometer’s Sketchpad Software with Jean Piaget's theory-based Constructivism approach; 2) determine the effectiveness of the Mathematics Learning CD assisted by Geometer’s Sketchpad Software with Jean Piaget's theory-based Constructivism approach. The method used in this research is research and development or research and development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research is grade VIII-4 SMP St. Petrus Medan with 32 students. The type of data used is qualitative data and quantitative data. Based on data processing and discussion, the data obtained from the material expert validation results with a percentage of 85.4% are in the category of very valid, while the results of the validation of media experts with an average percentage of 87.3% are in the category of very valid so that the mathematics learning CD is said to be very valid . The effectiveness of mathematics learning CD assisted by geometer's sketchpad software with constructivism approach based on Jean Piaget's Theory can be seen from the following assessments: 1) Positive responses assessed by students with an average percentage of positive responses of 88.88% with a very positive category, and responses teachers with an average percentage of 84% with a positive category; 2) the results of observations of teacher activities in managing learning using CDs learning mathematics with an average percentage of 89.73% with very good categories and the results of observations of student activities with an average percentage of 86.66% with very good categories; 3) the test results of student learning outcomes is obtained classical completeness of 84.37% with a very high category. Based on these assessments it can be concluded that the use of mathematics learning CDs assisted by geometer’s sketchpad software with Jean Piaget's theory-based constructivism approach is valid and effective in the learning process.